O município como um sistema político: exercício de poder para o ordenamento territorial em Senador José Porfírio – PA - SILVA, Robson Leocadio da (Universidade Federal do Pará, 2023)
In this present master’s degree dissertation we seek to present a research related to the territorial planning of the municipality of Senador Jose Porfirio - State of Para, which inserted the Amazonian territorial context, presents itself as the only city that has a discontinuous territory. The territorial planning requires establishing interrelationships with a high degree of complexity, involving political conflicts, which can generate impasses and new spatial configurations. The territorial planning establishes government guidelines as new definitions of powers are established in the territory, with challenges imposed on municipal administrations and the influences created by a globalized policy. The municipality, on the other hand, is an institution thought of as an administrative tool that has been shaping itself on the European continent and is inserted in Brazil by its colonizers, that has always been seen in an inferior position compared to other units of federation (Federal and Government). After a historical formation that dates back to the 17th century (1639), Senator Jose Porfirio, which was once one of the largest municipalities territorially in the world, that was once named Souzel, reaches the present day with its separate territorial limits, after the emancipation of the municipalities of Anapu and Vitória do Xingu in the early 1990s. With the socio-economic dynamics established in the region and the implementation of large projects such as UHE Belo Monte and Volta Grande Gold, the occupation of the territory intensified, putting pressure on municipal management with basic demands such as health, education and road maintenance. The present research will try to analyze the possible implications in the territorial management of the municipality of Senador Jose Porfirio. Considering the context of discontinuity, municipal public management and territoriality, since it is imperative to strengthen the latter to achieve sustainable development.